The evaluating of pregnancy-associated plasma protein-A with the likelihood of small for gestational age - Maryam Sadat Hoseini; Samaneh Sheibani; Mehrdad Sheikhvatan (Korean Society of Obstetrics and Gynecology, 2020)
ObjectiveRecently, strong evidences were obtained on the association between low pregnancy-associated plasma protein-A (PAPP-A) levels in the first trimester and poor outcomes of pregnancy.MethodsThis cross-sectional study was conducted on all pregnant women who were referred to the Obstetrics and Gynecology Clinic at Imam Hossein Hospital in Tehran, Iran in 2014. Women were asked to attend clinical examinations and screening at 11-14 weeks of gestation.ResultsBased on the definition, 14.5% of neonates found to be small for gestational age (SGA). There was a strong association between PAPP-A levels and birth weight. The mean PAPP-A level in the mothers of neonates who were SGA was significantly lower than those without this poor outcome. Based on the receiver operating characteristic curve analysis, serum PAPP-A level was a main determinant in the prediction of SGA neonates.ConclusionThe serum PAPP-A level at 11-13 weeks of gestation can effectively predict the increased risk for fetal growth retardation. In patients in this study, the best cutoff value for PAPP-A was 0.75 MOM, which signifies that lower levels of this marker can predict fetal growth restriction with high sensitivity and specificity.